PENINGKATAN LITERASI DIGITAL MELALUI GAME WORDWALL DALAM MATA PELAJARAN AKIDAH AKHLAK KELAS VIII - Lailatun Nufus; Nur Wiji Sholikin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of students’ digital literacy in Akidah Akhlak learning remains a challenge, particularly due to the dominance of traditional lecture-based instruction. This study aimed to enhance students’ digital literacy through the implementation of the Wordwall game as a learning medium in Grade VIII Akidah Akhlak at SMP Namira, Probolinggo City. The study employed a quantitative approach with a quasi-experimental design. The research subjects consisted of 30 students, divided into 15 students in the experimental class and 15 students in the control class, selected based on their level of understanding of the concepts of honesty and trustworthiness. The research was conducted from October 18 to 22, 2025. Data were collected through pretests and posttests, interviews, and documentation. The results showed that the average score of the experimental class increased from 54.6 to 67.3, while the control class experienced only a relatively low improvement. These findings indicate that the use of the Wordwall game is effective in improving students’ digital literacy and fostering more active and meaningful learning.